Synthesis and Antiinflammatory Properties of N-Substituted Guanidines - Pathak, Santosh; Singh, Dhananjay; Prakash Singh, Ved (Asian Journal of Chemistry, 2011)
Various N[(p-substituted/unsubstituted)phenyl), (substituted thiazol-2-yl/oxazol-2-yl/ naphthothiazol-2-yl)],N'-[N"',N"'-dimethyl/diethylaminoacetyl],N"-phenyl guanidines were prepared from corresponding N-substituted thiocarbamides and were evaluated for their antiinflammatory activity. All the substituted guanidines (100 mg/Kg) provided 1-79 % protection against carrageenin induced edema in rats. Phenyl butazone (100 mg/Kg) was used as a standard drug for comparative evaluation and showed greater antiinflammatory activity. The results suggest that the presence of methoxy group on phenyl nuclei at para position enhances antiinflammatory activity. The increase in chain length on alkyl group of N (R)2 skeleton also cause some enhancement in activity. Among heterocyclic molecules maximum level of antiinflammatory activity is shown by oxazol-2-yl substituted guanidines.